GE_GERICHTE P/13611/2017 vom 11. Oktober 2017 - GE Cour de justice (2017)
MENACE(DROIT PÉNAL) ; INJURE ; DISPOSITIONS PÉNALES DE LA LCR ; EXCÈS DE VITESSE ; FIXATION DE LA PEINE | CP.180.al1; CP.177.al2; LCR.90.al2; CP.47